DEVELOPING READING SKILLS THROUGH INTERACTIVE METHODS FOR VOCATIONAL COLLEGE LEARNERS (American Journal of Interdisciplinary Research and Development, 2024)
This essay examines the use of interactive teaching strategies to enhance reading skill development among vocational college students. The literature review highlights the limitations of traditional, passive instructional approaches in building the necessary reading competencies for this population. In contrast, the study's findings demonstrate that incorporating collaborative discussions, application-based activities, and explicit strategy instruction can significantly improve reading comprehension and strategy use. Qualitative data further reveals increased student engagement, improved technical text understanding, and more positive attitudes towards reading. The results contribute to the theoretical understanding of interactive pedagogy and provide practical implications for reading instruction in vocational college programs.